Optimal Road Route Selection Criteria System for Oversize Goods Transportation - Darius Bazaras; Nijolė Batarlienė; Ramūnas Palšaitis; Artūras Petraška (The Baltic Journal of Road and Bridge Engineering, 2013)
The criteria system described in this paper is suitable to be used for planning and designing oversize or heavyweight cargo transportations routes. This system gives the possibility to choose objectively the most suitable sections of the route in existing road network. Also it is a means to compare various routes in the same certain territory allowing objectively selecting the best one according the certain criteria. The paper indicates that criteria system is an efficient mean for comparing the existing heavyweight and oversize cargo transportation routes for various modes of transport with alternatives of building new ones or building/redesigning some parts of the route.